2007
DOI: 10.1021/bm070062i
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Ionic Liquids in Carbohydrate Chemistry:  A Window of Opportunities

Abstract: Ionic liquids (ILs) are composed only of ions. Of special interest to this review are those where at least one ion (the cation) is organic and whose melting points are below or not far above room temperature. ILs are designated as "green" solvents because they have extremely low vapor pressure, are non-inflammable, and thermally and chemically stable. Therefore, many of them can be, in principle, recycled into the process indefinitely. The objective of the present review is to discuss different aspects of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
310
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 625 publications
(314 citation statements)
references
References 170 publications
2
310
0
2
Order By: Relevance
“…The large size and conformational flexibility of the ILs ions lead to small lattice enthalpies and large entropy changes [2,3]. Therefore, the liquid state of ILs is thermodynamically favorable.…”
Section: Introductionmentioning
confidence: 99%
“…The large size and conformational flexibility of the ILs ions lead to small lattice enthalpies and large entropy changes [2,3]. Therefore, the liquid state of ILs is thermodynamically favorable.…”
Section: Introductionmentioning
confidence: 99%
“…As for 1-butyl-3-methylimidazolium chloride ([bmim][Cl]), Remsing et al (2006) and Moulthrop et al (2005) have reported that the chloride anion is much more involved than the cation in the disruption of the hydrogen bond system (18 to 25 wt.%) and the solubilization of the chains. The postulated Cl-OH-cellulose interaction is comparable to the structure discussed for the cellulose/DMAc/LiCl system, but it should be more efficient because the anion is free due to its looser binding with the large asymmetric cation (El Seoud et al 2007).…”
Section: Introductionmentioning
confidence: 66%
“…Cellulose, a biocompatible, biodegradable, nontoxic, and inexpensive natural material, is well soluble in [BMIm]Cl and other ILs with melting points below 100 C. 100 Theoretical aspects of the interaction of cellulose and some cellulose-based materials with ILs have been discussed in previous reviews. [29][30][31][32]101 The solubility of cellulose in ILs depends on the origin, extent of polymerization, temperature of the dissolution, and water content in the system, in particular. [30][31][32]102 Cellulose can be regenerated from the cellulose-IL solutions in a variety of forms (films, fibers, beads, sponges, etc.)…”
Section: ·1·2 Ionic Liquids In Cellulose Dissolution/regenerationmentioning
confidence: 99%
“…ILs can dissolve inorganic gases (O2, CO2, CO, SO2, NO2, H2S, etc. ), 24,27 silicon alkoxides (tetramethoxysilane, TMOS; tetraethoxysilane, TEOS; methyltrimethoxysilane, MTMOS), 28 mono-and polysaccharides (carbohydrates, starch, cellulose, chitin, chitosan, guar gum, and xanthan gum), 10,[29][30][31][32] natural organic materials (silk 17 and wood 29,33,34 ), some synthetic polymers, 35,36 enzymes, [37][38][39] etc. The listed substances can serve either as matrix materials (natural and synthetic polymers) or recognition elements (dyes, complexes, and biocatalysts), and target compounds (gases) for optical sensing platforms.…”
Section: Introductionmentioning
confidence: 99%